Examination of correlation of levels of alveolar bone loss in interdental and interradicular space using radiographic analysis - Pejčić Ana S.; Kostić Milena M.; Obradović Radmila R.; Stanković Ivana V.; Minić Ivan Z.; Igić Marko A.; Gligorijević Nikola R. (Medicinski fakultet i Klinika za stomatologiju, Niš, 2023)
Introduction: One of the consequences of the presence of periodontitis is the loss of alveolar bone in the interdental and interradicular space. Bone loss is very important for assessing the severity of the disease and applying therapeutic procedures. Aim: The objective was to determine and compare the loss of interdental and interradicular alveolar bone using radiographic analysis. Material and methods: 100 patients, aged 40 to 60 years, with chronic periodontitis and involvement of grade III and IV furcations in mandibular molars were examined. After orthopantomographic imaging, morphological measurements of mesial and distal interdental bone loss were performed, as well as the measurements of interradicular space. Then, their interrelationship was analyzed. Results: The mean value of mesial interdental bone loss was 5.90 ± 2.4mm, and the mean value of distal was 6.1 ± 6.1mm, while the mean value of interradicular bone loss was 3.55 ± 5.1mm. The correlation between interradicular and interdental bone loss was statistically significant (p<0.001). A higher correlation was present in respondents older than 50 years compared to younger respondents. Regarding gender, no statistically significant difference was observed between the examined bone levels. Interradicular bone loss of 0.8 mm and more was observed in subjects with bone loss in the interdental area of at least 3.7 mm. Conclusion: The results show that there is a correlation between the loss of alveolar bone levels in the interdental and interradicular space of the molars in chronic periodontitis, so interdental and interradicular bone loss can be used as an additional test in diagnosing the disease. Additional research is needed, which would include the use of three-dimensional radiography to determine the severity of the disease and therapeutic procedures.